THE MEANING OF THE WORD ‘CRY’ ON CORPUS OF CONTEMPORARY AMERICAN ENGLISH: SYNTACTIC AND SEMANTIC STUDY - Alia Nur Fitriyani; Deden Novan Setiawan Nugraha (Universitas Widyatama, 2021)
This research title is “The Meaning of The Word ‘Cry’ on Corpus of Contemporary American English: Syntactic and Semantic Study”. The purposes of this research are to analyze the syntactic category and to analyze the meaning of the word ‘cry’ on Corpus of Contemporary American English. The methods used in this research are distributional method to analyze the syntactic category and identity method to analyze the meaning of the word ‘cry’. The steps for the research are collect the data which is the sentence that has the word ‘cry’ on Corpus of Contemporary American English, then analyze the syntactic category and the meaning of the word ‘cry’. The data source is the sentence that has the word ‘cry’ on the Corpus of Contemporary American English website. The theoretical basis used in identifying syntactic categories are O'Grady's (1993) theory and Chaer's (1994) theory to identify the types of meanings The results showed that out of 32 data that have been analyzed, the lexical category was obtained, namely 25 verb data (78.12%) and 7 noun data (21.87%). Meanwhile, the types of meanings found are 11 data of lexical meaning and grammatical meaning (34.37%), 10 data of contextual meaning (31.25%), 8 data of lexical meaning (25%), 2 data of contextual meaning and grammatical meaning (6.25%), and 1 data of connotative meaning (3.12%).